2022
DOI: 10.1001/jamanetworkopen.2022.39336
|View full text |Cite
|
Sign up to set email alerts
|

Use of US Food and Drug Administration Expedited Drug Development and Review Programs by Orphan and Nonorphan Novel Drugs Approved From 2008 to 2021

Abstract: ImportanceThe US Food and Drug Administration (FDA) has 4 programs that can be used alone or in combination to expedite drug availability: Accelerated Approval, Breakthrough Therapy, Fast Track, and Priority Review. Drugs using these programs can include novel drugs, which do not contain a previously FDA-approved active moiety, and orphan drugs, intended for diseases or conditions affecting fewer than 200 000 people; to date, no comprehensive evaluation of how these programs have been used in combination has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…1(p31) The FDA's subsequent approval of Relyvrio represents the agency's increasingly flexible approach, prioritizing earlier access over evidentiary certainty. 2,3 However, the FDA has not typically shown proportionate flexibility in exercising its postmarket authorities, taking a narrow approach to requiring postmarket efficacy studies to confirm benefit. 4 Moreover, when these studies have been required, the FDA has often not strictly enforced deadlines and has been hesitant to withdraw approval even after substantial delay or failure of completed studies to demonstrate benefit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1(p31) The FDA's subsequent approval of Relyvrio represents the agency's increasingly flexible approach, prioritizing earlier access over evidentiary certainty. 2,3 However, the FDA has not typically shown proportionate flexibility in exercising its postmarket authorities, taking a narrow approach to requiring postmarket efficacy studies to confirm benefit. 4 Moreover, when these studies have been required, the FDA has often not strictly enforced deadlines and has been hesitant to withdraw approval even after substantial delay or failure of completed studies to demonstrate benefit.…”
Section: Introductionmentioning
confidence: 99%
“…The FDA’s subsequent approval of Relyvrio represents the agency’s increasingly flexible approach, prioritizing earlier access over evidentiary certainty . However, the FDA has not typically shown proportionate flexibility in exercising its postmarket authorities, taking a narrow approach to requiring postmarket efficacy studies to confirm benefit .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the ability to deliver on unmet medical needs has driven the use of a variety of accelerated review options to deliver therapies to patients faster. A recent study on the use of various expedited drug development and review programs offered by the US Food and Drug Administration (FDA) between 2008 and 2021 revealed that 97 of 139 (70%) approved biologic products used one or more expedited programs (Monge et al, 2022). This is good news for patients but only if manufacturing can meet patient demand.…”
Section: Introduction—current Challengesmentioning
confidence: 99%
“…In the Original Investigation titled “Use of US Food and Drug Administration Expedited Drug Development and Review Programs by Orphan and Nonorphan Novel Drugs Approved From 2008 to 2021,” 1 published November 1, 2022, the numbers in parentheses on the x-axis were incorrect in Figure 1B, C, E, and F. This article has been corrected. 1 …”
mentioning
confidence: 99%